2007
DOI: 10.1063/1.2787972
|View full text |Cite|
|
Sign up to set email alerts
|

Generation of fast propagating combustion and shock waves with copper oxide/aluminum nanothermite composites

Abstract: Nanothermite composites containing metallic fuel and inorganic oxidizer are gaining importance due to their outstanding combustion characteristics. In this paper, the combustion behaviors of copper oxide/aluminum nanothermites are discussed. CuO nanorods were synthesized using the surfactant-templating method, then mixed or self-assembled with Al nanoparticles. This nanoscale mixing resulted in a large interfacial contact area between fuel and oxidizer. As a result, the reaction of the low density nanothermite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
96
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(97 citation statements)
references
References 14 publications
(13 reference statements)
1
96
0
Order By: Relevance
“…This approach involves the 104 organization of the plane front of the combustion wave propagat- 105 ing in one direction; recording the linear velocity of reaction front 106 propagation; the study of the thermal structure of the wave; the 107 identification of controlling stages and burning patterns. The nov- 108 elty was already in the fact that the metallothermy was not studied 109 as a process of metallurgy, but as a combustion process. Such 110 approach led further to the discovery of other (non-thermite) type 111 of combustible systems, which can be used for synthesis of 112 materials.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…This approach involves the 104 organization of the plane front of the combustion wave propagat- 105 ing in one direction; recording the linear velocity of reaction front 106 propagation; the study of the thermal structure of the wave; the 107 identification of controlling stages and burning patterns. The nov- 108 elty was already in the fact that the metallothermy was not studied 109 as a process of metallurgy, but as a combustion process. Such 110 approach led further to the discovery of other (non-thermite) type 111 of combustible systems, which can be used for synthesis of 112 materials.…”
mentioning
confidence: 98%
“…This 1167 characteristic makes composites a promising candidate for fast-im-1168 pulse microthruster applications [108]. It was found that 1169 nanothermite composites are capable of producing shock waves 1170 with Mach numbers up to 2.44 in an air-filled tube [109]. In general, 1171 micro-and nano-electromechanical systems and sensors are extre-1172 mely promising fields for nanothermites [110].…”
mentioning
confidence: 99%
“…Rather, they undergo a rapid defl agration driven by an oxidation-reduction reaction (i.e., M 1 + M 2 O → M 2 + M 1 O + Δ E ). The linear fl ame propagation velocity is a commonly used metric to describe their reactivity and, to date, most research efforts have focused on enhancing kinetics by decreasing the mixing scale between constituents through mechanical milling, [ 11 ] core-shell [ 12 ] or laminate structures, [ 13,14 ] self-assembly, [ 15 ] or by replacing micrometer particles with nano particles. [ 16 ] While these methods have been shown to improve reactivity, further advances will likely be limited by processing constraints such as particle size, degree of mixing, passivation, sensitivity, and cost.…”
mentioning
confidence: 99%
“…4 Packed or patterned nanoenergetic materials are suitably utilized in various applications such as safe arm and re devices, 3 microthrusters 5 molecular gene delivery 6 as well as pyrotechnic microinitiators.…”
Section: Introductionmentioning
confidence: 99%